THE INFLUENCE OF INSTAGRAM PROMOTION ON UMRAH PRODUCT PURCHASE DECISIONS AT PT KAISA ROSSIE TOUR AND TRAVEL - Vivian Valentina; Budi Astuti (Publikasi Inspirasi Indonesia, 2025)
This study aims to analyze the influence of Instagram promotion strategies on consumer purchasing decisions at PT Kaisa Rossie Tour & Travel. Using a quantitative approach, data were collected through online questionnaires distributed via Google Forms to 200 consumers who had used the company’s services. The data were analyzed using simple linear regression with the assistance of SPSS software. The analysis reveals that Instagram promotion has a positive and significant effect on consumer purchasing decisions, indicating that more effective promotional activities lead to a higher tendency among consumers to make a purchase. This finding highlights the crucial role of digital promotion strategies in shaping consumer behavior, particularly in the travel and tourism industry. The results provide practical implications for PT Kaisa Rossie Tour & Travel in formulating marketing strategies that utilize Instagram more effectively to enhance purchasing decisions.